Effect of Different Extracts of Ganoderma lucidum on Ochratoxin A Formation by Aspergillus ochraceus - Marzieh Vahdani; Shahram Shoeibi*; Anousheh Sharifan (Iranian Society of Pharmacognosy, 2022)
Background and objectives: Mycotoxins are secondary metabolites produced by fungi contaminated agricultural products and have toxic effect in human and animals. Ochratoxin A is produced by many filamentous fungi species such as Aspergillus and Penicillium, and is classified as a possible carcinogen and nephrotoxic. Ganoderma lucidum is a famous mushroom with antifungal properties and probably preventive effect on toxin production. The aim of this study was to investigate the antitoxigenic properties of Iranian strain of G. lucidum as a natural antitoxigenic agent against harmful filamentous fungi in food industry. Methods: Different extracts of G. lucidum were prepared and the antifungal and antitoxigenic effects were studied on toxigenic Aspergillus ochraceus. Ethanolic, hydroalcoholic and aqueous extracts were prepared by cold maceration method and compared with commercial extracts. Ochratoxin A was analyzed by high performance liquid chromatography (HPLC) coupled with fluorescence detector in A. ochraceus culture media which was treated with the extracts. Results: The results expressed that the alcoholic extracts could inhibit fungal growth but the aqueous extracts were able to significantly prevent toxin production while the fungus totally grew. Conclusion: Ganoderma lucidum and its products, may be used as a pharmaceutical and nutraceutical mushroom and could be considered as safe and useful agents for prevention of fungal growth and mycotoxin formation in food and agricultural products.